Kandungan Fosfor Tanaman Padi dan Emisi Karbon Tanah Gambut yang Diaplikasi dengan Amelioran Fe3+ dan Fosfat Alam pada Beberapa Tingkat Pemberian Air - Nelvia, . (UNIVERSITY OF LAMPUNG, 2009)
The addition of ameliorant Fe3+ and rock phosphates containing high Fe cation can reduce effect of toxic organic acids, increase peat stability through formation of complex compounds and reduce carbon emission. The research was conducted in the laboratory and green house of the Departement of Soil Science, Faculty of Agriculture, Bogor Agriculture University. Peat samples with hemic degree of decomposition were taken from Riau. Rock phosphates were taken from the rock phosphates of PT. Petrokimia Gresik, Christmas Island phosphates, and Huinan China and FeCl3.6H2O was used as the other Fe3+ source. The aims of the research were to study (a) the effect of the applications of ameliorant Fe3+ and rock phosphates on the P content of plants dan (b) the effect of the application ameliorant Fe3+ and the contribution of Fe cation in rock phosphates in the decrease of carbon emission. The results showed that the P content of plants rice increased 58 – 286 % with the applications of ameliorant Fe3+ and rock phosphates. The estimation of carbon loss through CO2 and CH4 emissions from peats if planted continuously with rice was around 2.5, 2.2 and 2.6 Mg of C ha-1 year-1 respectively in field capacity condition, two times of field capacity condition, and 5 cm of saturated condition. The application of ameliorant Fe3+ and rock phosphates containing high Fe cation increased the stability of peats and reduced the carbon loss around 1.7 Mg of C ha-1 year-1 (64%) in 5 cm of saturated condition, 1,3 Mg of C ha-1 year-1 (58%) in two times of field capacity condition, and 1.0 Mg of C ha-1 year-1 (41%) in field capacity condition.